Biological control of leaf diseases in soybean (Research, Society and Development, 2023)
The soybean crop has been increasingly highlighted on the national scene. Great strides and improvements in productivity have been achieved. However, there are still limiting factors that influence its performance, mainly foliar diseases. Therefore, the present research aims to evaluate the performance of the biofungicide, Bacillus subtilis BV02, in the control of foliar diseases in soybean. The test was carried out at the Semear experimental station, with a completely randomized block design (DBC), with 4 replications and 6 treatments. Observations were made through evaluations of leaves in the lower, middle and upper thirds, comparing them with the diagrammatic scales. Furthermore, defoliation, disease incidence, yield, and thousand-grain weight (PMG) were analyzed. Initially, a low pressure of the brown spot was obtained, but at the end of the cycle the disease intensified together with other DFC, where treatments 3 and 6 obtained better results. Asian rust, on the other hand, showed a high incidence, resulting in early defoliation in treatments 1, 4 and 5, while in treatments 3, 2 and 6, good control was observed. Treatment 3 had similar productivity to T6, so that T2 stood out, where the productivity of T2 was similar to T5. Therefore, the use of a biological fungicide associated with a chemical one presents better results, so that biofungicides can be an important tool in the integrated management of foliar diseases, which impact crop productivity.